The impact of different left ventricular geometric patterns on right ventricular deformation and function in the elderly with hypertension: A two-dimensional speckle tracking and three-dimensional echocardiographic study - Xue, Jiping; Kang, Xiaoyan; Qin, Qin; Miao, Junwang; Li, Shuai; Kang, Chunsong (Frontiers in Cardiovascular Medicine, 2022)
Objective: To evaluate the impact of different left ventricular geometric patterns on right ventricular deformation and function in elders with essential hypertension via two-dimensional speckle tracking and three-dimensional echocardiography. Methods: A total of 248 elders with essential hypertension were divided into four groups based on the left ventricular mass index (LVMI) and relative wall thickness (RWT): the normal geometric, concentric remodeling, eccentric hypertrophy, and concentric hypertrophy groups. Moreover, 71 participants were recruited as the control group. These participants were examined by two-dimensional speckle tracking and three-dimensional echocardiography to obtain the right ventricular strain parameters and three-dimensional volume and function parameters. Results: The right ventricular strain parameters decreased gradually from the normal geometric group to the concentric hypertrophy group (P < 0.05), and the strain parameters in the concentric remodeling, eccentric hypertrophy, and concentric hypertrophy groups were lower than those in the control and normal geometric groups (P < 0.05). The right ventricular three-dimensional echocardiographic parameters only changed in the eccentric hypertrophy group (P < 0.05) and concentric hypertrophy group (P < 0.05) in the form of increasing volume and decreasing function. Multivariate linear regression analysis showed that the right ventricular free wall longitudinal strain was independently associated with the systolic blood pressure (SBP), LVMI, and RWT (P < 0.05) and primarily affected by the LVMI (normalized β = 0.637, P < 0.05). Conclusion: The systolic function of the right ventricular myocardium declined in the elders with essential hypertension due to impaired myocardial mechanics. Compared with the right ventricular three-dimensional volume and function parameters, the right ventricular strain parameters could indicate mechanical damage in the concentric remodeling group earlier. The right ventricular free wall longitudinal strain was primarily subject to the LVMI.